Gradient copolymers versus block copolymers: self-assembly in solution and surface adsorption. Issue 35 (9th August 2022) - Coldstream, Jonathan G.; Camp, Philip J.; Phillips, Daniel J.; Dowding, Peter J.
Abstract : Coarse-grained molecular dynamics simulations reveal that the molecular conformations, self-assembly, and surface adsorption of block, gradient, and statistical copolymers show different sensitivities to temperature. Abstract : The structures of amphiphilic block and gradient copolymers in solution and adsorbed onto surfaces are surveyed using molecular-dynamics simulations. A bead-spring model is used to identify the general effects of the different architectures: block and gradient copolymers have equal numbers of solvophilic and solvophobic beads, and the gradient copolymer is represented by a linear concentration profile along the chain. Each type of isolated copolymer forms a structure with a globular head of solvophobic beads, and a coil-like tail of solvophilic beads. The radius of gyration of a gradient copolymer is found to be much more sensitive to temperature than that of a block copolymer due to an unravelling mechanism. At finite concentrations, both gradient and block copolymers self-assemble into micelles, with the gradient copolymers again showing a larger temperature dependence. The micelles are characterised using simulated scattering profiles, which compare favourably to existing experimental data. The adsorption of copolymers onto structureless surfaces is modelled with an attractive potential that is selective for the solvophobic beads, and the surface structures are characterised using the average height of the molecules, and the proportion of beads adsorbed. Both types of copolymer form adsorbed films with persistent micelle-like structures, but the gradient copolymers show a stronger dependence on the strength of the surface interactions and the temperature. Coarse-grained, bead-spring models allow a rapid survey and comparison of the block and gradient architectures, and the results set the scene for future work with atomistic simulations. A superficial but favourable comparison is made between the results from the bead-spring models, and atomistic simulations of a butyl prop-2-enoate/prop-2-enoic acid (butyl acrylate/acrylic acid) copolymer in n -dodecane at room temperature.